Alternatives to local content requirements in resource-rich countries. (2nd October 2017) - Kolstad, Ivar; Kinyondo, Abel
Abstract: This paper discusses whether and to what extent resource-rich developing countries should introduce local content policies, i.e. requirements to include local inputs in petroleum extraction activities of multinational corporations. We argue that local content needs to be seen as a public expenditure question, since local content requirements increase multinational costs, and hence reduce the taxes which can be extracted from these companies. This implies that there are opportunity costs in imposing local content requirements, since the forgone taxes can be used in others ways which could potentially do more to improve development prospects. Moreover, past experiences of resource-rich developing countries suggest that local content policies can exacerbate key problems of patronage and rent-seeking which resource rents generate, increasing the chance that the resource wealth will prevent rather than help development. These arguments suggest that an optimal local content policy in the context of flawed institutions is a more limited one than those typically pursued by developing countries with recently discovered petroleum reserves. Using qualitative data from Tanzania, a country with recent discoveries of substantial natural gas deposits, we analyze why local content tends to become such a central issue in debates and policy processes, despite its potentially problematic aspects.